Resistance, early engagement and outcome in psychoanalytic psychotherapy of patients with psychosomatic disorders. Issue 4 (December 2016) - Yasky, Jaime; King, Robert; O'Brien, Tom
Abstract: Background: Difficulties engaging people with psychosomatic disorders in psychotherapy are widely recognised. Such patients are often reluctant to participate in psychotherapy and to consider the contribution of psychological factors to their somatic experience. However, less is known about effective ways to address what is commonly referred to as resistance to psychotherapy among this population. Objectives: To study early engagement, client resistance and the impact of therapist response on outcome in treatment of psychosomatic disorders. Methodology: Mixed methods were used in a naturalistic longitudinal study of 22 psychotherapeutic treatments of patients with psychosomatic disorders. Results: Persistence with treatment was associated with better outcome. The extent to which therapists addressed patients' in‐session distress was associated with persistence with treatment, even when distress was not resolved. Discussion: Results do not allow attribution of causality but indicate that further research investigating therapist recognition of and response to client distress may be important in the development of more effective psychotherapeutic response to people with psychosomatic disorders.